Icon of the Blessed Regina Protmann as a Form of Transmission of Faith - Sonak, Dariusz (Studia Warmińskie, 2014)
The 400th anniversary of the death of blessed Regina Protmann was an opportunity to contemplate once more her life, her work and charisma, which was her gift from God. Her spirituality must be read anew as a practical model of following the evangelical guidelines. The Catholic Church is undergoing a kind of renaissance in the popularity of icons. An icon painted as a celebration of the anniversary of her death is a concrete form of the transmission of faith that she lived by as well as a proposal to join her spiritual message as expressed in the words: as God wishes! By her life devoted to God and the Church, she reminds us that the essence of a consecrated life lies in contemplating His mystery in prayer as well as serving the sick, the poor and the rejected.